A AN EXPLORATORY STUDY ON THE POSITION AND SIZE OF NATURAL AIR OPENINGS AS A PASSIVE VENTILATION STRATEGY IN SPACE - achmad najma irdiansyah; Heru Subiyantoro (DEARSIP : Journal of Architecture and Civil, 2025)
The issue of climate change in the world has become a serious problem until now. The excessive use of artificial air conditioning systems is one of the main contributors to climate problems in the world. Design solutions to help the world's climate problems through a design approach that creates optimal natural air conditioning performance. One of the things that affects the performance of natural ventilation is the placement of the opening position based on the Velocity of the airflow. Soori Bali designed by SCDA Architects was chosen as the object of study because the orientation of the building is designed to take advantage of the potential of the sea breeze as a natural ventilation strategy in its resort units. The method used is the simulation method using Autodesk CFD by evaluating several variations in the position and size of the openings placed horizontally from the left side to the right side of the building. The data collected included the airflow velocity (m/s), flow direction, and turbulence position to the layout of the room in each variation. The results of the simulation were compared to determine the most effective opening and furniture configuration configuration in supporting natural ventilation in tropical buildings. The results of the study showed that the 3 × 3 meter openings placed in the middle position of the room were able to produce an air flow of 1–3 m/s with a temperature distribution of 25–27°C, thus creating optimal passive thermal comfort in tropical buildings in accordance with the SNI 03-6572-2001 standard.